Pengaruh Kualitas Layanan dan Harga terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Hotel Zodiak di Kota Bandung - Olive Caroline; Chandra Kuswoyo (Universitas Kristen Maranatha, 2013)
This research wanted to understand the influence of service quality and price againts customer loyality through customer satisfaction. This research used quantitative approach. The object of this research is specified for Zodiac Hotel’sconsumers in Bandung. The data used is primer data that obtained from 210 respondents and sampling method used is purposive sampling. The data obtained and analyzed by using Structural Equation Modeling (SEM). Where obtained thatthe value of Tstatistic on service quality (9.39) > Ttable (1.97), the value of Tstatistic on price (1.01) < Ttable (1.97), and the value of Tstatistic on customer satisfaction (8.49) >Ttable (1.97). The result of this research showed that service quality affects customer satisfaction and customer satisfaction impact loyalty, while the price is considered no effect on customer satisfaction and customer loyalty. The conclusion of this research was a significant effect on service quality and customer satisfaction impact loyalty Zodiac Hotel ‘consumers.